Fire in the Early Palaeolithic: Evidence from burnt small mammal bones at Cueva Negra del Estrecho del Río Quípar, Murcia, Spain. (October 2016) - Rhodes, S.E.; Walker, M.J.; López-Jiménez, A.; López-Martínez, M.; Haber-Uriarte, M.; Fernández-Jalvo, Y.; Chazan, M.
Abstract: The development of pyrotechnology is a hallmark of human history, providing our ancestors with warmth, security and cooked food. Evidence for fire use before 400 thousand years ago (kya) remains contentious due largely to the taphonomically fragile nature of charcoal and ash. As such, it is imperative to the study of prehistoric fire that we develop techniques and methodologies for identifying anthropogenic fire use via more robust materials. A new methodology described by Fernández-Jalvo and Avery (2015) based on small mammal taphonomy to identify high intensity fire events from the distant past is replicated herein. When we applied this method to assemblages from Cueva Negra del Estrecho del Río Quípar, an upland rock-shelter in southeastern Spain, dated to between 780 kya and 980 kya, we recognized a spatial relationship between highly heat modified micromammal specimens and a previously reported delineated feature of thermally altered and carbonate rich sediment which also includes heat-fractured chert and calcined bone (the fire feature). The proportion of heavily heat-modified specimens (charred and/or calcined specimens) identified within the stratigraphic context associated with the fire feature proved statistically significant ( x 2 = 169.18, p < 0.001) when compared with the proportion of similarly modified specimens from overlying deposits (within other stratigraphic layers). The degree of discolouration seen on the micromammal remains within the fire feature has been linked to temperatures exceeding 600 °C (Shipman et al., 1984), and as such supports claims that the fire feature may have an anthropogenic origin. Environmental scanning electron microscopy and energy dispersive spectroscopy (SEM-EDS) of bone specimens confirms that this discolouration is due to burning rather than post-depositional mineral staining. This confirms that methodology, which represents a novel line of evidence for identifying pyrotechnical events at early Palaeolithic sites, can be used to identify potentially anthropogenic fire events from the distant past when alternative scenarios are excluded. Furthermore, studies of this type showcase the value of including detailed taphonomic studies of microfauna assemblages within multidisciplinary research projects. Highlights: The Fernández-Jalvo & Avery method using small mammal bone for identifying fire features is applied at Cueva Negra Microfauna is used to test the identification of fire events at the Lower Paleolithic site of Cueva Negra SEM-EDS analysis is applied to differentiate thermal discolouration from oxide-staining on small mammal bones The spatial distribution of burning on microfauna provides useful proxy evidence for studies of prehistoric fire